Design and implementation of a potato peeling prototype - Diaz Mána, Jeisson Orlando; Ordierez , Laura Daniela (I+ T+ C- Research, Technology and Science, 2020)
This document describes the design and construction of a prototype of peeled potatoes with recycled material, in order to create a frozen potato processing line to meet the current demand in Colombia as it grows every year. national production is quite low and fails to meet national demand, this problem is due to various factors such as the difficulty of acquiring credits to this industry to improve its productivity, the low production of potatoes that this industry needs and the lack of government support and this led to low productivity in the agricultural sector since potatoes are being imported and we are not producing it with this project, we can combat this problem. In the study process the market for this type of machines was analyzed, such as the manufacturer and country of origin. In the software, the Arduino microcontroller was used for its efficiency and ease of use, the motor was controlled with a simple power circuit since the motor and other components operate at more than 120 v, the design was carried out through SolidWorks and a yield of 100 kg / hour is expected, which will be peeled and washed for its next process, this will shorten the production time in the potato peeling and cleaning treatment.